Masses and widths of scalar–isoscalar multi-channel resonances from data analysis; Journal of Physics G: Nuclear and Particle Physics; Vol. 41, iss. 2 - Surovtsev Y. S.; Bydzovsky P.; Kaminski R.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Nagy M. (2014, 2014)
Title screen